2013
DOI: 10.1074/jbc.m113.504365
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Synaptojanin 1 Accelerates Aβ Clearance and Attenuates Cognitive Deterioration in an Alzheimer Mouse Model

Abstract: Background: Recent studies have linked synaptojanin 1 (synj1) with Alzheimer disease (AD). Results: We report that synj1 reduction decreases amyloid plaque burden and attenuates cognitive deterioration in an AD mouse model. These effects are mediated through accelerating endosomal/lysosomal degradation of A␤. Conclusion: Our data suggest a novel mechanism by which synj1 reduction promotes A␤ clearance. Significance: These studies implicate a therapeutic strategy for AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
64
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 50 publications
9
64
0
Order By: Relevance
“…One such pathway may be aberrant metabolism of membrane phospholipids. Recent literature, including data from our laboratory, suggests that PI homeostasis, particularly PIP 2 , plays an important role in AD (10,22,24,28,29). For example, one study demonstrated PIP 2 reduction in the prefrontal cortex of patients with AD (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One such pathway may be aberrant metabolism of membrane phospholipids. Recent literature, including data from our laboratory, suggests that PI homeostasis, particularly PIP 2 , plays an important role in AD (10,22,24,28,29). For example, one study demonstrated PIP 2 reduction in the prefrontal cortex of patients with AD (29).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicates that phospholipid regulators including synj1 (22)(23)(24), phospholipase D (25), and PI-binding clathrin assembly protein (26) play important roles in pathways leading to neurodegenerative processes such as lipid granule accumulation, endosomal/lysosomal degradation, and regulation of microglia and astrocyte functions. Our data show that ApoE3 increases brain PIP 2 levels through promotion of synj1 mRNA degradation and suppression of synj1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in the dose of the chromosome 21 gene cystatin B (CSTB), which encodes an endogenous inhibitor of lysosomal cathepsins, decreases the accumulation of Aβ and associated cognitive deficits 147 . Overexpression of another chromosome 21 gene, synaptojanin 1 (SYNJ1), which encodes a phosphoinositide phosphatase that regulates levels of membrane phosphatidylinositol-4,5-bisphosphate, has been associated with endosomal enlargement 148 , whereas reduced expression of SYNJ1 lowers Aβ accumulation, as well as neuronal dysfunction and cognitive deficits 149,150 . How endosomal enlargement caused by trisomy contributes to neuronal dysfunction and degeneration is another important area for future research.…”
Section: Disruption Of Secretory and Endosomal Systemsmentioning
confidence: 99%
“…For example, herbal medicines and isolated compounds have been [191][192][193] and of diabetic neuropathy 194 . Here, we will focus on two major areas: antimicrobials, and modulators of protein protein interactions.…”
Section: Opportunities For Natural Productsmentioning
confidence: 99%